2022
DOI: 10.1002/adfm.202209767
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Ion Permselectivity in MXene/MOF Nanofluidic Membranes for High‐Efficient Blue Energy Generation

Abstract: Both ion permeability and selectivity of membranes are crucial for nanofluidic behavior. However, it remains a long‐standing challenge for 2D materials to balance these two factors for osmotic energy harvesting. Herein, the MXene/metal–organic framework (MOF) hybrid membranes are reported to realize efficient ion‐permselective nanofluidic system, leading to high‐performance osmotic power generator. In the system, zeolitic imidazolate framework‐8 (ZIF‐8) is deposited onto the MXene surface and intercalated betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 48 publications
0
22
0
1
Order By: Relevance
“…Meanwhile, the maximum power density reached 9.7, 5.91, and 3.84 W m −2 under testing areas of 0.03, 1, and 5 mm 2 , respectively (Figure S18b). Such a size effect on the power density widely exists in the previous reports, 31,32 which could be attributed to the stronger ion concentration polarization caused by pore−pore interactions under a large membrane size. 4 The stability of the V-NbP membrane was tested by an H cell configuration in Figure S9.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Meanwhile, the maximum power density reached 9.7, 5.91, and 3.84 W m −2 under testing areas of 0.03, 1, and 5 mm 2 , respectively (Figure S18b). Such a size effect on the power density widely exists in the previous reports, 31,32 which could be attributed to the stronger ion concentration polarization caused by pore−pore interactions under a large membrane size. 4 The stability of the V-NbP membrane was tested by an H cell configuration in Figure S9.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…7−9 This worldwide blue energy can be gathered by nanofluidic systems with cation-or anion-exchange nanochannels using membrane technologies, such as pressureretarded osmosis (PRO) 10 and reverse electrodialysis (RED). 11,12 Among them, RED attracts significant attention as it can directly transform the electrochemical potentials into electrical energy, and its applications are closely related with the nature of the ion exchange nanochannel membranes. 13−17 In recent years, various ion exchange nanochannel membranes with enhanced ion selectivity and high mass flux, such as single-layer MoS 2 nanopores, 18 mesoporous carbon/anodic aluminum oxide (AAO), 19 ordered mesoporous silica/AAO, 20 heterogeneous MXene/PS-b-P2VP, 21 polyamide modified graphene oxide/AAO, 22 polymer polystyrenesulfonate (PSS) incorporated metal organic framework (MOF)/AAO, 23 bacterial cellulose nanofiber/GO, 24 and sulfonated poly(ether ketone)/AAO/polypyrrole composite membrane 25 devices.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Owing to the exhaustion of traditional nonrenewable resources and increasingly severe global environmental problems, it is necessary to strike a better balance between energy security, environmental protection, and economic development. As an abundant, sustainable, renewable, and stable energy resource, salinity gradient energy between the seawater and river water, which is also known as “blue energy”, can be harvested. In theory, 0.8 kW of energy can be produced from every cubic meter water since the chemical potential differences are constructed with the salt concentration differences, which is almost comparable with the hydrostatic pressure energy that is harvested from a 280 m high water column. This worldwide blue energy can be gathered by nanofluidic systems with cation- or anion-exchange nanochannels using membrane technologies, such as pressure-retarded osmosis (PRO) and reverse electrodialysis (RED). , Among them, RED attracts significant attention as it can directly transform the electrochemical potentials into electrical energy, and its applications are closely related with the nature of the ion exchange nanochannel membranes. In recent years, various ion exchange nanochannel membranes with enhanced ion selectivity and high mass flux, such as single-layer MoS 2 nanopores, mesoporous carbon/anodic aluminum oxide (AAO), ordered mesoporous silica/AAO, heterogeneous MXene/PS- b -P2VP, polyamide modified graphene oxide/AAO, polymer polystyrenesulfonate (PSS) incorporated metal organic framework (MOF)/AAO, bacterial cellulose nanofiber/GO, and sulfonated poly­(ether ketone)/AAO/polypyrrole composite membrane have been explored to assemble into salinity gradient power conversion devices. However, not only the competition of selectivity and permeability but also the instability and high cost of these nanochannel membranes have led to the low power density and further limit their realistic scale-up applications. , Thus, it is still necessary to develop a new type of nanochannel membrane through designing and controlling the characteristics of the nanomaterials to handle these practical challenges. , …”
Section: Introductionmentioning
confidence: 99%
“…30 Zhou et al used intercalated ZIF-8 to shorten the transport pathway of ions in a MXenes membrane and obtained a ∼3.9 kΩ internal resistance and high output power density. 31 Wu et al and Wen et al showed that PVMs 16 and holey GO 17 nanosheets can be reconstituted as low-resistance nanochannels, respectively. Tam et al and Wen et al realized the reduction of transport resistance by enlarging the nanochannel space through bulky cellulose nanocrystals (CNC) 22 and cellulose nanofibers (CNF), 23 respectively.…”
Section: Introductionmentioning
confidence: 99%